Development and Evaluation of Goat Milk Tablet Using Dry Granulation Techniques for Nutraceutical Purposes - Aminuddin, Azfar; Mohd Akmal, Azhar (Penerbit Universiti Malaysia Pahang, 2017)
There are several problems for the school children to take the pure milk especially the goat milk every day because of the unpleasant taste and smell of the goat milk are not so good. Besides, the pure milk has a short life time. It is difficult to store the goat milk in a long period of time at room temperature. The solution for this problem is change the goat milk from liquid form into the chewable milk tablet that can be easily consume by the school children. Goat milk in the form of tablet formulation will increase the shelf life of the product. Therefore, the chewable goat milk tablet can be stored in a long period of time, convenience, and suitable for distribution to remote areas. In this project, the focusing was more into the optimization of the weight adjustment of the tableting machine before and after the dry granulation to form good chewable tablet. The pre-evaluation had been done for the goat milk powder and granule after dry granulation process. It can be concluded that goat milk tablet can be an alternative to the pure goat milk. The poorly flowing properties of goat milk powder can be improved by using dry granulation techniques. Based on this study, F4D shows the best setting to produce the goat milk tablet using dry granulation technique. F4D suc cessfully improved the flow ability and compressibility of goat milk tablet. It also produce the best goat milk tablet as it possess uniformity of weight, low friability and good hardness.